BERALIH DARI MEBEL KAYU SOLID KE MEBEL BERBASIS ROTARY VENEER (BENTWOOD) - Susi Hartanto (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2022)
AbstractWith spindleless rotary peeling technology, small diameter wood (such as rubber wood, acacia, or coconut) became possible to be processed into rotary veneers, compared to previous technologies that only allowed for large diameter wood, which is now increasingly rare. The purpose of this article is to provide insight, especially for furniture designers to utilize raw materials that are more environmentally friendly and efficient, but still have the beauty of wood. This article was compiled using a descriptive analysis method, direct study through the manufacture of various wooden furniture made from solid wood on a mass production scale and prototype-scale veneer (bentwood) furniture, surveys to factories that produce solid wood furniture, and surveys to factories that produce rotary veneers and bentwood. Rotary veneers converted to bentwood furniture is a more environmentally friendly, sustainable, efficient option in the use of materials, parts, and hardware.Keywords: rotary veneer, bentwood, furniture   AbstrakDengan teknologi rotary peeling spindleless, kayu berdiameter kecil (seperti kayu karet, akasia, dan kelapa) menjadi mungkin untuk diproses menjadi rotary veneer, dibandingkan teknologi sebelumnya yang hanya memungkinkan untuk kayu berdiameter besar, yang saat ini sudah semakin langka. Tujuan dari artikel ini adalah memberikan wawasan, terutama bagi desainer mebel untuk lebih memanfaatkan bahan baku yang lebih ramah lingkungan dan efisien, namun tetap memiliki keindahan kayu. Artikel ini disusun dengan metode analisis deskriptif, studi langsung melalui pembuatan berbagai mebel kayu berbahan kayu solid skala produksi masal dan mebel berbahan veneer (bentwood) skala prototipe, survei ke pabrik yang memproduksi mebel kayu solid, dan survei di pabrik yang memproduksi rotary veneer dan bentwood. Rotary veneer yang dikonversi menjadi mebel bentwood adalah pilihan yang lebih ramah lingkungan, berkelanjutan, efisien dalam penggunaan material, part, dan hardware. Kata kunci: rotary veneer, bentwood, mebel